BEING AN URBAN WOMAN: A Marxist Feminist Study On The Main Female Character In Ika Natassa's A Very Yuppy Wedding - Sutjiati Ely Sativani, - (2010)
The research entitled "Being an Urban Woman: a Marxist Feminist Study on the Main Female Character in Ika Natassa's a Very Yuppy Wedding" aims to identify the presentation of the main female character and the influence of urban society towards the main female character as evidenced in the novel. The research is qualitative descriptive with textual analysis approach. The research employs Marxist feminist theory proposed by Tong (2009) as the framework. The result of analysis shows that the main female character is presented as an urban woman who is modern and has economic values. The research also finds that the urban society as evidenced in the novel influences the main female character to be an independent woman. Since women in urban society are financially independent, their role gradually changes from being a housewife into being a career woman.